2004
DOI: 10.1111/j.1478-4408.2004.tb00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reactive dyes upon the uptake and antibacterial action of poly(hexamethylene biguanide) on cotton. Part 1: Effect of bis(monochlorotriazinyl) dyes

Abstract: Poly(hexamethylene biguanide) (PHMB) is of interest as a bactericide for fabrics. It has affinity for cotton by reaction with the cellulosic carboxylate groups. In this study, the capacity of undyed cotton to absorb PHMB has been determined and compared with cotton dyed with anionic bis(monochlorotriazinyl) reactive dyes. When cotton is dyed with these dyes the absorption of PHMB increases, the dye providing sulphonic acid sites with which the PHMB can react. The reacted PHMB and the percentage fixation of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Regarding their volume, nanoparticles have a high specific surface area. By decreasing the size of a particle, its surface distribution rate increases [87]. The quantity of adsorbed silver on untreated bleached/ mercerized cotton was 32 ppm when 30 nm silver nanoparticles were used and 13 ppm when 80 nm silver nanoparticles were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding their volume, nanoparticles have a high specific surface area. By decreasing the size of a particle, its surface distribution rate increases [87]. The quantity of adsorbed silver on untreated bleached/ mercerized cotton was 32 ppm when 30 nm silver nanoparticles were used and 13 ppm when 80 nm silver nanoparticles were used.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of moisture, silver cations react with hydroxyl functional cellulosic groups and are attached to each other electrostatically. The presence of a reactive dye on cotton and the introduction of additional covalently bound sulfonic acid groups will facilitate the uptake of a cationic antimicrobial agent [87]. Therefore, it is possible to conclude that RucoBac AGP is bound to the cotton surface through sulfonic groups of a covalently bound dye and through partially ionized hydroxyl and carboxyl groups present on the fiber [72].…”
Section: Resultsmentioning
confidence: 99%
“…PHMB [Fig. 1(A)] was reported to absorb UV light,10 probably because of the CN double bonds in the structure. We confirmed that PHMB absorbed UV with a single sharp peak at wavelength of 236 nm [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between PHMB and the PMS/sulfite‐treated wool surface is a matter of interest. Because of its cationic nature, PHMB attachment on cotton has been found to be predominantly due to ionic interaction with the carboxylic acid at low concentrations and hydrogen bonding at higher concentrations 9, 10. The dyeing of cotton fabrics with reactive dyes, which introduces additional anionic sulfonic groups in the fabric, further increases the uptake of PHMB 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation